The Faifi Arabic [St] Reflex of Ṣād: Proto-Semitic or Substrate? - Davis, Stuart (Journal of Semitic studies, 2022)
This paper argues against the view that the unusual reflex of ṣād as [st] in Faifi Arabic stems from a metathesized version of the Proto-Semitic glottalized affricate * cʾ([tsʾ]), as in Alfaifi and Behnstedt (2010: 53-4), where [st] is assumed to pattern as monosegmental. Instead we propose that the [st] reflex of ṣād in Faifi Arabic reflects a South Arabian ejective or glottalized fricative *sʾ as a substrate feature. We first argue that Faifi Arabic [st] patterns as bisegmental based on linguistic argumentation internal to the dialect. We then discuss *s’as a feature of South Arabian varieties that can be considered as part of the Faifi substrate. We then detail how it is phonetically plausible for ejective sʾ to ‘break’ into a sequence of a fricative followed by a stop, such as [st], accounting for its bisegmental patterning and its realization as pharyngealized [ṣ] where [st] is phonotactically impossible.